2021
DOI: 10.1021/acs.chemmater.1c01941
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of Magnetite Mesocrystals: Interplay between Nanoparticle Morphology and Solvation Shell

Abstract: Nanoparticle assemblies with long-range packing order and preferred crystallographic orientation of building blocks, i.e., mesocrystals, are of high interest not only because of their unique physical properties but also due to their complex structure and morphogenesis. In this study, faceted mesocrystals have been assembled from the dispersion of truncated cubic-shaped iron oxide nanoparticles stabilized by oleic acid (OA) molecules using the nonsolvent “gas phase diffusion technique” into an organic solvent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Furthermore, a variation in the crystallographic arrangement of the PtNCs in mesocrystals from OLA, LOA, or LLA is unlikely given the results of preceding work where it is shown that the crystal structure of a gas‐phase diffusion self‐assembled mesocrystal is dictated by the solvent and stabilizer concentration rather than its number of C═C double bonds [14a,19] . These findings conclude that the increasing facet‐to‐facet particle distance, which we examined in the 2D self‐assemblies, must be taking effect within the 3D mesocrystals as well and are the primary contributor to the decrease in conductivity.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, a variation in the crystallographic arrangement of the PtNCs in mesocrystals from OLA, LOA, or LLA is unlikely given the results of preceding work where it is shown that the crystal structure of a gas‐phase diffusion self‐assembled mesocrystal is dictated by the solvent and stabilizer concentration rather than its number of C═C double bonds [14a,19] . These findings conclude that the increasing facet‐to‐facet particle distance, which we examined in the 2D self‐assemblies, must be taking effect within the 3D mesocrystals as well and are the primary contributor to the decrease in conductivity.…”
Section: Discussionmentioning
confidence: 57%
“…This approach was already successfully applied for the analysis of the averaged structures and defects in single colloidal grains of gold and magnetite nanocrystals Schlotheuber ne ´Brunner et al, 2021). We expect that it will find applications for understanding the structure of colloidal grains and single crystals in future.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we demonstrated an application of the AXCCA for qualitative determination of the crystalline structure of a colloidal crystal, including the present planar defects. AXCCA provides a complementary view on the structure when CDI reconstruction does not work (Schlotheuber ne ´Brunner et al, 2021). The results can be interpreted by means of a simple geometrical model of the crystalline lattice and defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, solvent quality plays a significant role in the extension of the ligand layer and the hydrodynamical shape (i.e., the volume of the surface ligand shell increases when its solvation degree increases). 2,3,27,50,51 Notably, depending on the mesocrystals under investigation, other factors need to be considered for the eventual controlled growth of 3D binary mesocrystals. For instance, in some cases, high nanoparticle concentrations can favor the formation of bcc structures 53,54 (i.e., generally associated with the absence of long-range order at the atomic level).…”
Section: Effective Shapementioning
confidence: 99%